Reading Positions, the Cow Bell Effect, and the Sounds of Silent Film - Altman, Rick (Cinémas)

(untitled) (Cinémas, 1992)
This article demonstrates that both the historical hypothesis and the hermeneutic hypothesis are misleading in the approach regarding the problems of reception. Studying certain performance practices of American silent film, the author concludes that instead of positing cultural conditions for audiences as the basic catalyst for changes in reception, we need to pay greater attention to the capacity of texts to contain and control their own reception.